The Cambridge history of war. (New York, NY Cambridge, UK ; New York, NY)
<2> cilt (2. c. xiv, 748 sayfa ; 4. c. xiii, 656 sayfa)
Keywords: “Volume II of The Cambridge History of War covers what in Europe is commonly called 'the Middle Ages'. It includes all of the well-known themes of European warfare, from the migrations of the Germanic peoples and the Vikings through the Reconquista, the Crusades and the age of chivalry, to the development of state-controlled gunpowder-wielding armies and the urban militias of the later middle ages; yet its scope is world-wide, ranging across Eurasia and the Americas to trace the interregional connections formed by the great Arab conquests and the expansion of Islam, the migrations of horse nomads such as the Avars and the Turks, the formation of the vast Mongol Empire, and the spread of new technologies – including gunpowder and the earliest firearms – by land and sea“ -- “Volume IV of The Cambridge History of War offers a definitive new account of war in the most destructive period in human history. Opening with the massive conflicts that erupted in the mid nineteenth century in the US, Asia and Europe, leading historians trace the global evolution of warfare through 'the age of mass', 'the age of machine' and 'the age of management'. They explore how industrialization and nationalism fostered vast armies whilst the emergence of mobile warfare and improved communications systems made possible the 'total warfare' of the two World Wars. With military conflict regionalized after 1945 they show how guerrilla and asymmetrical warfare highlighted the limits of the machine and mass as well as the importance of the media in winning 'hearts and minds'. This is a comprehensive guide to every facet of modern war from strategy and operations to its social, cultural, technological and political contexts and legacies“ --